Neuropeptide Y prolongs non-social memory and differentially affects acquisition, consolidation, and retrieval of non-social and social memory in male mice - Johannes Kornhuber; Iulia Zoicas (Scientific Reports, 2017)
Abstract Neuropeptide Y (NPY) and its receptors (especially Y1, Y2, and Y5) are highly expressed in brain regions involved in learning and memory processes. Accordingly, NPY was shown to modulate cognitive functions in rodents. Here, we investigated possible memory-enhancing effects of NPY and determined the role of the NPY system in the acquisition, consolidation, and retrieval of non-social and social memory in mice, using the object and social discrimination tests, respectively. Intracerebroventricular (icv) infusion of NPY (1 nmol/2 µl) prolonged retention of non-social (object) memory, but not of social memory. This effect was blocked by the Y1 receptor antagonist BIBO3304 trifluoroacetate (2 nmol/2 µl), but not by the Y2 receptor antagonist BIIE0246 (2 nmol/2 µl). While icv infusion of NPY did not affect the acquisition, consolidation, and retrieval of non-social and social memory, icv infusion of BIBO3304 trifluoroacetate and BIIE0246 blocked the consolidation of non-social memory and the retrieval of both non-social and social memory. This study suggests that NPY has memory-enhancing effects in a non-social context by specifically acting on Y1 receptors. It further suggests that the central NPY system exerts differential effects on the sequential phases of non-social and social memory.